Animals as Symbols of Human Positive and Negative Traits on Javanese Expressions - Tri Wahyu Setiawan Prasetyoningsih; Dyah Raina Purwaningsih; Nadia Gitya Yulianita (Bina Nusantara University, 2020)
The research aimed to analyze the metaphor of animals’ names in Javanese expressions as representing power and authority in its positive and negative sides. The ancient land of Java was ruled by kings. This situation indicated that ancient Javanese were closely related to kingdoms and regulations that were strict rules of politeness rules or authoritarian. It created a situation where direct criticisms, suggestions, and warnings were conveyed to those who had power, which might cause the problem to the conveyor. Thus, people preferred to express their opinion in the metaphorical form to preserve the Javanese manners. Since Javanese people also lived as farmers and hunters, they could identify the nature of various animals’ characters. They began to compare some animals’ nature characters to describe human characters or behaviors in the forms of metaphor known as Javanese expressions. The methods applied were a descriptive qualitative by choosing the data that contained animal names, classifying them, analyzing the meanings of the expressions, and providing results of the analysis. These metaphorical forms are hitherto known as proverbs and are make used them as philosophy of life. They also used proverbs. The data were taken from “Seri Kajian Sastra Klasik 100 Paribasan Jawa Simpul-Simpul Kearifan Lokal Budaya Jawa” by Bambang Husen Al Marie in 2018. There are 26 expressions using animal names found in this dictionary. Macan, gajah, and asu are the three animals that are mostly used as a metaphor to describe human characters within a sovereignty. Heuristic and hermeneutic approaches are applied to analyze the data and to find out the real meaning of the classified data.